Prevalence of Bacteroides and Prevotella spp. in ulcerative colitis - Lucke, Katja; Miehlke, Stephan; Jacobs, Enno; Schuppler, Markus (Journal of medical microbiology, 2006)
1 Institute of Medical Microbiology, Canton Hospital Luzern, Switzerland 2 Medical Department I, University Hospital Dresden, Germany 3 Institute of Medical Microbiology and Hygiene, Technical University Dresden, Germany 4 Laboratory of Food Microbiology, Institute of Food Science and Nutrition, Swiss Federal Institute of Technology Zurich, ETH Center LFV B21, Schmelzbergstrasse 7, CH-8092 Zurich, Switzerland Correspondence Markus Schuppler Markus.Schuppleratilw.agrl.ethz.ch Received 10 June 2005 Accepted 28 December 2005 The resident bacterial flora of the large intestine has become increasingly recognized as an essential component in the pathogenesis of ulcerative colitis (UC). However, it is still not known whether the bacterial flora in general or certain bacterial species of the intestinal microbial flora contribute to the pathogenesis of the disease. In order to investigate the composition of the mucosa-associated microbial flora in UC, mucosal tissue samples from patients with active UC and from control subjects with non-inflammatory conditions were analysed and compared. To cover the whole spectrum of intestinal bacteria and to circumvent the known bias introduced by culture-based techniques, comparative 16S rRNA gene sequence analysis was used to determine the bacterial composition in the mucosal tissue samples. The investigation revealed an abundance of sequences from Bacteroides spp. and Prevotella spp. in the mucosal tissue of patients with UC compared with individuals showing no signs of disease. The higher incidence of populations of members of the Bacteroidetes in UC suggests that these may have an influence on the pathogenesis of the disease. Abbreviations: DIG, digoxigenin; IBD, inflammatory bowel disease; UC, ulcerative colitis. The GenBank/EMBL/DDBJ accession numbers for the 16S rRNA gene sequences determined in this study are AJ812137 AJ812212 .